The economic costs and health-related quality of life of people with HIV/AIDS in the Canary Islands, Spain - Oliva-Moreno Juan; Lopez-Bastida Julio; Perestelo-Perez Lilisbeth; Serrano-Aguilar Pedro (BMC, 2009)
Abstract Background The objective was to determine the economic burden, as well as the impact on HRQOL for people with HIV/AIDS in Spain in 2003. Methods A cross-sectional study of 572 people with HIV were recruited from outpatient clinics in the Canary Islands, Spain. Demographic, health resources utilization, indirect costs and quality of life data were collected through medical records and questionnaires filled out by people with HIV. HRQOL was measured with two generic questionnaires: SF-36 and EQ-5D. Results In 2003 annual costs of caring for patients with asymptomatic HIV, symptomatic HIV and AIDS were €10,351, €14,489 and €15,750, respectively. The HRQOL with the EQ-5D was 0.78. SF-36 summary results for physical and mental health were 48.30 and 38.80, respectively. Conclusion HIV/AIDS represent a high economic impact from society point of view. the structure of health care costs have changed due to these new drugs, increasing the weight of pharmaceutical treatment over total costs and decreasing the importance of inpatient care costs. In spite of the therapeutic improvements, labour losses/indirect costs still represent a high cost. Costs and HRQOL were strongly associated with severity. Although the latest drug developments have not yet been able to find the definitive cure, they have allowed an improvement in expectancy of life and in the HRQOL of the patients.